Interventions of Iranian Traditional Medicine for Constipation During Pregnancy - F Hashem Dabaghian; M Taghavi Shirazi; F Amini Behbahani; A Shojaee (Institue of Medicinal Plants, ACECR, 2015)
Background: Constipation is a common complaint during pregnancy. Iranian Traditional Medicine (ITM) has some recommendations for this complaint. Objective: In this study, interventions of constipation in pregnancy have been presented and their efficacy and safety evidence were reviewed from modern literature. Methods: Interventions selected based upon the chapters related to health protection of pregnant women from ITM literature. Then a literature search was performed in the scientific databases including articles from inception up to March 2014. Articles with a focus on safety or efficacy of the selected herbs during animal or human pregnancy were selected. Results: Folus (Cassia fistula), Shir-khesht (Cotoneaster numularia Fisch.), Tamarind (Tamarindus indica), Taranjabin (Alhagi camelorum), Damask rose (Rosa damascene) and almond oil are the most recommended medications for constipation in pregnant women. For all of these herbs, there is some efficacy evidence in animal or human studies. Folus is forbidden during pregnancy due to its anthraquinones ingredients. Shir-Khesht was safe in a study to treatment of constipation in pregnant women. The other mentioned herbs have not been evaluated during pregnancy. There is limited evidence to provide safe advice for consuming these herbs for constipation during pregnancy. Conclusion: Although there are some animal and human study suggesting the laxative effect of ITM interventions, their safety are not sufficiently documented in modern literature. Scientific studies regarding these herbal remedies during pregnancy and pregnancy outcome are warranted to determine safety.